Preliminary evaluation of genetic variability for seedling morphology among selected varieties of cowpea [Vigna unguiculata (L.) Walp.] - Ajeigbe, Hakeem A.; Ewansiha, S.U.; Singh, B.B. (2007)
A preliminary trial was conducted to determine if there were variabilities in seedling morphology of selected cowpea varieties and determine their heritability with aim that this could be used in future cowpea breeding for selection at seedling stage. The characters studied include hypocotyl, epicotyl and plant height. Variabilities were found among the cowpea varieties for these characters. The values for heritability were 81, 74 and 83% for hypocotyl, epicotyl and plant height respectively. Seed size had very low correlation with the seedling characters. It is recommended that further studies should be carried out to investigate the relationship between the seedling characteristics and general growth characteristics of cowpea including grain and fodder productivities. This may provide a valuable tool for cowpea breeders to make selections at seedling stages and help in resource allocations in the breeding programs.